Repeated Measures of Cervicovaginal Cytokines during Healthy Pregnancy: Understanding “Normal” Inflammation to Inform Future Screening - Buxton, Miatta A.; Meraz-Cruz, Noemi; Sánchez, Brisa N.; Foxman, Betsy; Gronlund, Carina J.; Beltran-Montoya, Jorge; Castillo-Castrejon, Marisol; O'Neill, Marie S.; Vadillo-Ortega, Felipe (American Journal of Perinatology, 2020)
Objective This study aimed to describe characteristics of cervicovaginal cytokines obtained during pregnancy from women who subsequently delivered at term.Study Design We used repeated measures of 20 cervicovaginal cytokines, collected on average on a monthly basis, from the second to the ninth month of gestation among 181 term pregnancies in the Mexico City Pregnancy Research on Inflammation, Nutrition, & City Environment: Systematic Analyses cohort (2009–2014). Cytokines were quantified using multiplex assay.Results Cytokine distributions differed more between than within cytokines. Across trimesters, cytokines interleukin (IL)-1Ra, IL-1α, and IL-8 consistently had high concentrations compared with other measured cytokines. Cytokine intraclass correlation coefficients ranged from 0.41 to 0.82. Spearman's correlation coefficients among cytokine pairs varied but correlation directions were stable; 95.3% of the 190 correlation pairs remained either negative or positive across trimesters. Mean longitudinal patterns of log-transformed cytokines from Tobit regression varied across but less within cytokines.Conclusion Although mean concentrations of cervicovaginal cytokines among term pregnancies were high, they were largely stable over time. The high cytokine concentrations corroborate that pregnancy is associated with an active inflammatory state. These characterizations may serve as a baseline for comparison to other obstetric outcomes, which may be helpful in understanding deviations from normal gestational inflammation.
Keywords: appropriate statistical methods; cytokines; inflammation; patterns; longitudinal data; pregnancy; PRINCESA cohort; Tobit regression; term birth